MODEL BIMBINGAN KESEHATAN MENTAL UNTUK PARA SANTRI PONDOK PESANTREN SYAFIâ€™IYAH CISAMBENG MAJALENGKA - Yedi Supriadi (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2017)
The goalÂ of the researchÂ areÂ to describeÂ the development of the mental healthÂ for young students at the boardingÂ school in the islamic school of Syafi'iyyah in Cisambeng city ofÂ Palasah-MajalengkaÂ regency.Â DevelopmentÂ ofÂ mentalÂ healthÂ inÂ questionÂ isÂ withÂ the planting of character and morals and a healthy mental approach to the students through some methode is calledÂ â€œshuhbahâ€ (friendship)Â for theÂ purposeÂ of mentalÂ development canÂ be achieved easily, accurately,Â effectively and efficiently. The method of the researchÂ are using descriptiveÂ Â methodÂ Â withÂ collectingÂ Â someÂ Â information,Â Â byÂ techniquesÂ Â gainedÂ Â through observation,Â interviews, questionnairesÂ and documentationÂ study. DataÂ retrievalÂ is derived from respondents who are seen mental health problems with a purposive sampling technique that aims to find out what the problem occurs in teenagersÂ these students then how after he followed theÂ guidanceÂ of mentalÂ healthÂ atÂ boardingÂ Syafi'iyyah CisambengÂ approachÂ by â€œshuhbahâ€ (friendship). Islamic conseling emphasizes spiritualÂ solutions based on love and fear of Allah and the duty of fulfil our responsibility as the servants of Allah on this earth.The results of the researchÂ illustrateÂ that the applicationÂ of mental health counseling with shuhbah (friendship) perceived benefit to the students who participatedÂ in mental health counseling becauseÂ after being interviewed and completed questionnairesÂ the students who have experienced problems of mental disordersÂ (misconduct) after obtaining calculatedÂ the mean category average high.Based on the recognitionÂ of the students,Â they areÂ feel much betterÂ afterÂ attending mental health trainingÂ activities in Pondok PesantrenÂ Syafi'iyyah Cisambeng guided by Mas Nawawi (Ustd.Muhamad Nawawi Fathulloh, M.Pd.I). Thus the results of this study presented a picture of the actual conditions in the field as the information and report the study authors.Â Keywords: Model Guidance, Mental Health,Â and Pupils